2020
DOI: 10.1002/adma.202000250
|View full text |Cite
|
Sign up to set email alerts
|

Metamaterials for Enhanced Optical Responses and their Application to Active Control of Terahertz Waves

Abstract: Metamaterials, artificially constructed structures that mimic lattices in natural materials, have made numerous contributions to the development of unconventional optical devices. With an increasing demand for more diverse functionalities, terahertz (THz) metamaterials are also expanding their domain, from the realm of mere passive devices to the broader area where functionalized active THz devices are particularly required. A brief review on THz metamaterials is given with a focus on research conducted in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 164 publications
0
39
0
Order By: Relevance
“…In this study, we rigorously demonstrated that the NWR branch ambiguity issue can be avoided by computing the proper right-inverse of the relationship (5) through the analytic continuation of a suitable analytic logarithm along the path determined in the complex plane by the scattering parameters of the MM under analysis. This prolongation has to be realized according to the formulation provided by Theorem 1, which states the conditions so that we can determine a unique solution for this problem.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we rigorously demonstrated that the NWR branch ambiguity issue can be avoided by computing the proper right-inverse of the relationship (5) through the analytic continuation of a suitable analytic logarithm along the path determined in the complex plane by the scattering parameters of the MM under analysis. This prolongation has to be realized according to the formulation provided by Theorem 1, which states the conditions so that we can determine a unique solution for this problem.…”
Section: Discussionmentioning
confidence: 99%
“…This clearly indicates that its preimage,γ(t), does not lie exclusively inside the strip (−π, π]. Thus, on the contrary of the previous case L(•) = log(•), and the analytic continuation has to be employed to solve (5). Since the point γ(a) (green diamond marker) lies on R + (as it must), the principal logarithm log(•) can and must be used as…”
Section: Numerical Experimentsmentioning
confidence: 95%
See 2 more Smart Citations
“…Recently, several groups reported their research progress in electrically tunable metasurface-based SLMs 68,72,137 . Although these works were based on different materials and methods, all of these designs were onedimensional (1D) metasurface-based SLMs.…”
Section: Discussion and Outlookmentioning
confidence: 99%